Perlindungan Konsumen dalam E-Commerce di Indonesia (Hambatan Penerapan Regulasi Antara Penerapan Dan Pengawasan) - Rosianna Evanesa Sihombing; Made Gede Subha Karma Resen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze consumer protection in e-commerce in Indonesia, focusing on the obstacles in implementing consumer protection regulations in e-commerce in Indonesia. It also aims to analyze and evaluate the challenges related to compliance and oversight in the application of consumer protection regulations. In the digital era, e-commerce transactions have rapidly evolved, but this has also led to various consumer protection issues, such as fraud and a lack of transparency. For that reason, appropriate regulations are needed to protect consumers. This research employs a normative-descriptive research method, utilizing both the statute approach and the conceptual approach. The author uses the statute approach to analyze the applicable laws related to e-commerce and consumer protection, while the conceptual approach is used to explore the ideal concept of consumer protection in the context of digital transactions. The research results indicate that although regulations related to e-commerce are in place, the main challenge lies in the less-than-optimal implementation and oversight. Obstacles such as a lack of human resources and monitoring technology, as well as the complexity of cross-border jurisdictions, are factors that complicate effective consumer protection. Therefore, there is a need for efforts to improve legal infrastructure and stricter oversight to ensure that consumer rights are protected within the e-commerce ecosystem in Indonesia.